Dewasa ini PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, DAN KEWAJARAN HARGA TERHADAP KEPUTUSAN PEMBELIAN - Dwipayana, Made Krisna; Mandala, Kastawan (E-Jurnal Manajemen, 2022)
The more aware the public of the importance of nutritious food for health derived from fruits, it causes more and tight competition in fruit stores to improve the decision to buy fruit from consumers. The purpose of this study is to explain the influence of product quality, quality of service and fairness of prices on fruit purchase decisions at The Super Fruit Shop In Anyar Sari Market Denpasar. The population used is consumers who have purchased UD products. Super Fruit located in Anyar Sari Market Denpasar. The sample used was 84 people. The analysis technique used is multiple regression analysis. The results of the analysis showed the quality of products, quality of service and fairness of the price had a positive and significant effect on the decision to purchase fruit at the Super Fruit Shop in Anyar Sari Market Denpasar. This means that the higher the quality of the product, the higher the quality of service and the better the perception of fairness of consumer prices on the products in the Super Fruit Market Anyar Sari Store will affect the purchase decision that is increasing Keywords: product quality, quality of service, fairness of price, purchasing decisions